Environmental Degradation and Fractured Identities in Nancy Huston’s Canadian Ecotexts - Kate Averis (Essays in French Literature and Culture, 2020)
In Brut: la ruée vers l’or noir (2015) and Le Club des miracles relatifs (2016), Nancy Huston contemplates the effect of fracking on the landscapes and communities of the Albertan tar sands of her native Canada. Reflecting a current and increasingly urgent global preoccupation with the threat posed by the destruction of the natural environment to the sustainability of the Earth’s ecosystems, these ecotexts draw a link between the degradation of the natural environment and the fracturing of human identities and relations. Employing an ecofeminist and extractivist critical framework, this article examines Huston’s use of both fictional and non-fictional writing in response to environmental destruction, the role fossil fuel extraction plays in this, and its social impacts. It concludes with a discussion of Huston’s ecoliterary project in view of her oft-repeated stance on the inadequacy of literature alone to respond to the current climate crisis.